Design and Analysis Three-Phase Shunt Active Power Filter in Mitigate Harmonic - Ab Shukor, Syahar Azalia; Mailah, Nashiren Farzilah; Mohd Radzi, Mohd Amran; Othman, Mohammad Lutfi; Abd Halim, Wahidah; Razi, Atikah; Borra, Venkata Silpa (Journal of Advanced Research Design, 2025)
Nowadays, the power electronic equipment is extensively employed across industrial, commercial, and residential consumers which inject harmonic current in the power system. These harmonics detrimentally affect power quality, precipitating various power quality issues. Due to the detrimental effects of harmonic currents, there is considerable research interest in mitigating their impact on power systems. In this context, a shunt active power filter (SAPF) stands out as the most dependable solution. Its operation involves initial detection of harmonic currents within contaminated power systems, followed by the generation and injection of corrective mitigation currents to eliminate the detected harmonics. This paper critically discussing and analyse control techniques for three-phase SAPFs aimed at enhancing power quality and mitigating current harmonics in nonlinear loads. The insights offered can serve as valuable guidance for selecting the optimal technique to synchronize SAPFs with connected power systems. Additionally, MATLAB/Simulink will be utilized to validate the efficacy of the SAPF in harmonic mitigation.